Strategi Pembelajaran Bahasa Arab dalam Upaya Mempersiapkan Calon Mahasiswa Baru ke Timur Tengah (Studi Kasus pada El-Darosah Banten) - Subhan; Zaki Ghufron; Dina Indriana; Azizah Alawiyyah; Mufrodi (Mantiqu Tayr: Journal of Arabic Language, 2024)
This article aims to analyze the Arabic language learning strategies implemented by El-Darosahat Banten in order to prepare prospective new students for the Middle East, especially Al-Azhar as the oldest university in Egypt. As we know that students who want to continue their studies in the Middle East have increased. Therefore, it requires a strategy in preparing Arabic so that they can follow learning in the Middle East well. This research is qualitative using descriptive analysis methods. Data were obtained through observation, interviews, and documentation studies. The qualitative approach according to Creswell allows a researcher to become a key instrument, namely as a data collector, behavioral observation, or participant interview. The object of research in this paper is students at the El-Darosah institution who want to continue their studies to the Middle East. The results of this research show that learning Arabic at this institution is for a specific purpose so that it has implications for several things: First, the implementation of Arabic learning at El-Darosah uses private and classical methods so that learning runs effectively; The material is a compilation of many resources pertaining to learning Arabic related to the acquisition of Arabic language skills; Third, in the grammatical aspect, students are required to identify and express ideas about the grammatical structure and style used in the texts provided, so that learning Arabic is more functional. Another strategy used in learning Arabic at this institution is that teachers always motivate students, so predetermined goals of learning Arabic can be achieved effectively and efficiently because students are present physically and psychologically. We recognize that this study has many flaws. Therefore, we hope that there are researchers who can continue our research, such as how the strategy of mastering the Amiyah language because outside of learning, the language used is the Amiyah language.